Le rôle de l’expérience et du collectif en situation de relève de poste - Valérie Le Bris; Ghislaine Tirilly; Cathy Toupin (Perspectives Interdisciplinaires sur le Travail et la Santé)
Shift handovers contribute to the continuity of the work process and the reliability of information relays between two teams. However, the formalization and organization of these transmission periods are more or less devised in response to each specific work situation. Many studies show that the information content and the way this information is relayed are the result of a collective activity in which experience plays an important role. Our article approaches the relations between experience and shift handovers through three studies from different sectors (hospital, aeronautical, and railroad). In our study, experience refers to the workers’ way of working (especially night work), but also to knowledge relative to the functioning of the work teams. The results show that changes in shift handover activity occurred to cope with the needs of the department and work team and that these changes should be taken into account in efforts to improve shift handover efficiency.